THE INFLUENCE OF CAREER DEVELOPMENT AND COMPETENCE ON EMPLOYEE WORK EFFECTIVENESS PT. AZURE SAMUDRA KARSA - Muhamad Wahyu Fatchurohman (Asosiasi Dosen Muda Indonesia, 2024)
This study aims to analyze how Career Development and Competence affect employee Work Effectiveness at PT. Azure Samudra Karsa. The findings show that both variables have a positive impact on work effectiveness overall. However, individually, only Career Development has a significant impact, making it the main factor in this context. Stepwise analysis reveals that Career Development (X2) has a greater influence than Competence (X1) in improving work effectiveness. Career development is understood as a planned process that includes individual awareness of personal career aspects and actions to achieve career goals throughout life. The conclusion of this study confirms that the career development program at PT. Azure Samudra Karsa has been effective and must be continued to improve employee work effectiveness. This study provides important guidance on the importance of career development for work effectiveness and suggests companies to continue to improve existing career development strategies.